2021
DOI: 10.3390/diseases9020026
|View full text |Cite
|
Sign up to set email alerts
|

Cleft Candidate Genes and Their Products in Human Unilateral Cleft Lip Tissue

Abstract: Cleft lip and palate are common congenital pathologies that affect the human population worldwide. The formation of cleft lip is associated with multiple genes and their coded proteins, which regulate the development of craniofacial region, but the exact role of these factors is not always clear. The use of morphological studies for evaluation of human cleft-affected tissue has been limited because of insufficiency of available pathological material. The aim of this study was to detect and compare the immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Furthermore, Shh signaling seems to promote pericyte-like function in cranial neural crest cells, which is necessary for microvascular stability and correct facial morphogenesis [ 63 ]. SHH has been associated with orofacial clefts in mice and human studies [ 26 30 ]. In our research, only 6 tissue samples had varying amounts of SHH gene-containing cells in the epithelium, but the results were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, Shh signaling seems to promote pericyte-like function in cranial neural crest cells, which is necessary for microvascular stability and correct facial morphogenesis [ 63 ]. SHH has been associated with orofacial clefts in mice and human studies [ 26 30 ]. In our research, only 6 tissue samples had varying amounts of SHH gene-containing cells in the epithelium, but the results were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there is a very limited amount of studies observing an association between SOX3 and orofacial clefts. For example, one study reported increased SOX3-positive immunoreactive structures within human unilateral cleft lip [ 30 ]. Therefore, while our data indicates that neither SHH nor SOX3 played a role in our study group, we cannot categorically exclude their role from CLP morhopathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cleft palate is thought to be an abnormality caused during palate development via one of the following mechanisms the left and right palatine processes are not elevated, and horizontal dislocation does not occur [6]; palatine processes are elevated but do not grow horizontally and do not make contact [7]; or left and right palatine processes make contact and do not fuse because of horizontal dislocation and horizontal growth of the palatine processes [8,9] and cleft palate, resulting in separation of the palate after fusion of the palatine processes [10,11]. Genetic factors include such as mutations in TGFβ, MSX1, TBX22, IRF6, and MEOX2, and Hoxc, HOXB3, and TFAP2A [12][13][14][15][16][17]. The multifactorial threshold theory suggests that environmental factors, such as alcohol and tobacco consumption, maternal obesity, and exposure to chemicals such as TCDD and vitamin A [18][19][20] interact to cause cleft palate once a certain threshold is exceeded.…”
Section: Introductionmentioning
confidence: 99%